Asymptotic analysis of the Stokes equations in a square at small viscosity. Issue 12 (1st December 2016) - Gie, G.-M.; Hamouda, M.; Sboui, A.
Abstract : Our aim in this article is to study the boundary layers appearing at small viscosity for the Stokes solutions in a square . By considering the Stokes problem in a square, we theoretically investigate the case where parabolic boundary layers are present. Using some divergence-free correctors, the asymptotic expansion of the viscous velocity solution is constructed and the uniform validity of the approximate solution is then proved.